Reduction of ROS-HIF1α-driven glycolysis by taurine alleviates Streptococcus uberis infection. Issue 4 (3rd February 2022) - Lan, Riguo; Zhou, Yuanyuan; Wang, Zhenglei; Fu, Shaodong; Gao, Yabing; Gao, Xing; Zhang, Jinqiu; Han, Xiangan; Phouthapane, Vanhnaseng; Xu, Yuanyuan; Miao, Jinfeng
Abstract : Antibiotic-resistant strains of Streptococcus uberis ( S. uberis ) frequently cause clinical mastitis in dairy cows resulting in enormous economic losses. Abstract : Antibiotic-resistant strains of Streptococcus uberis ( S. uberis ) frequently cause clinical mastitis in dairy cows resulting in enormous economic losses. The regulation of immunometabolism is a promising strategy for controlling this bacterial infection. To investigate whether taurine alleviates S. uberis infection by the regulation of host glycolysis via HIF1α, the murine mammary epithelial cell line (EpH4-Ev) and C57BL/6J mice were challenged with S. uberis. Our data indicate that HIF1α-driven glycolysis promotes inflammation and damage in response to the S. uberis challenge. The activation of HIF1α is dependent on mTOR-mediated ROS production. These results were confirmed in vivo . Taurine, an intracellular metabolite present in most animal tissues, has been shown to effectively modulate HIF1α-triggered metabolic reprogramming and contributes to a reduction of inflammation, which reduces mammary tissue damage and prevents mammary gland dysfunction in S. uberis -induced mastitis. These data provide a novel putative prophylactic and therapeutic strategy for amelioration of dairy cow mastitis and bacterial inflammation.